Combustion characteristics of fluoropolymer coated boron powders - Keerthi, Venu (2021)
The problem of sluggish combustion reactivity of Boron (B) can be overcome by inclusion of fluoropolymers. In this paper, three commercial fluoropolymers; PVDF (59 wt% F), Viton (66 wt% F) and THV (72 wt% F) coated (Ca. 4 wt%) B powders (Ca. 1-µm in size) were prepared and their combustion characteristics have been investigated. Among the fluoropolymer-coated powders, THV coated B provided the highest average improvement in heat of oxidation, reactivity in terms of pressure generation and combustion temperature followed by Viton and PVDF coated B. The sequence of reactivity enhancement has been explained by the variances in gasification efficiencies of the boric oxide shell, induced by the thermal decomposition of the respective fluoropolymer coatings. THV with higher fluorine and lower hydrogen content, supposedly promotes better gasification of the boric oxide shell by releasing more fluorine rich alkanes/alkenes during thermal decomposition. However, PVDF predominantly produces HF, which apparently less effective in gasification of the boric oxide shell, resulting in limited improvement of the measured properties.